Winterfield 2512 G-61 Strain of IBDV Vaccine (CEVAC® IBD L) Showed Reduced Pathogenicity in Commercial Chickens (Microbes and Health, 2013)
A live, freeze-dried commercial vaccine prepared from the Winterfield 2512 G-61 strain of infectious bursal disease virus (IBDV) was tested for its pathogenicity in commercial chickens. A total of 200 unvaccinated Cobb-500 chicks obtained commercial sources, raised in relative isolation from day old chick (DOC) were used in the experiment. A total of 3 chicks were randomly collected from the experimental flock on day 11 (D11), D13, D15, D17, D20, D23 and D26. The vaccine was administered through drinking water at D11 and the booster was also given on D17 through drinking water. All the sampled birds were euthanized for necropsy. The visible gross morbid lesions, bursa-body weight ratios and histomorphology including bursal lesion scores were recorded following necropsy and histopatholog. An infected flock was included in this study for comparison. Data of bursa-bodyweight ratios in relation to bursal lesion scores was analyzed statistically. No detectable gross lesions were found during necropsy and bursa-body weight ratios were 2.75±0.60, 2.71±0.39, 2.44±0.42, 3.39±0.13, 2.58±0.55, 2.15±0.16, 2.41±0.28 and 2.45±0.09 on D11, D13, D15, D17, D20, D23 and D26, respectively. Histopathological lesions were characterized as varying degrees of lymphoid depletion, and the bursal lesion scores were 0.67±0.33, 0.67±0.33, 2.00±0.58, 0.67±0.33, 1.0±0.00, 0.67±0.33 and 0.33±0.33 on D11, D13, D15, D17, D20 D23 and D26, respectively. The vaccine virus showed reduced levels of pathogenicity in broiler chickens. No disease outbreaks were noted in the vaccinated group, but significant changes were found in the naturally infected flock. DOI: http://dx.doi.org/10.3329/mh.v1i2.14091 Microbes and Health, 2012 1(2): 58-61